Governing police stops across Europe - Aston, Elizabeth; De Kimpe, Sofie; Fazekas, János; Lennon, Genevieve; Rowe, Michael (Palgrave's critical policing studies, 2024)
"This book takes a critical and comparative approach to the analysis of the governance of police stops across Europe. It draws on an EU COST Action research network on Police Stops which engaged academics and practitioners from 29 countries to better understand the practice of police stops. It begins by examining how police stops are defined and the various legal rules and levels of accountability afforded. The chapters are arranged by theme to focus on a core aspect of the governance of police stops. These include: legal frameworks and police discretion; internal governance; external accountability and civilian oversight; possibilities for legal recourse; and the different roles of data and technology. Each compares the distinct approaches evident across Europe, often employing case studies. The book adopts a critical approach, acknowledging governance as contested and involving diverse (state, non-state and supranational) actors. It considers implications for policing in a rapidly changing environment globally." --